2016
DOI: 10.1080/09168451.2016.1222264
|View full text |Cite
|
Sign up to set email alerts
|

Flavor characteristics of the juices from fresh market tomatoes differentiated from those from processing tomatoes by combined analysis of volatile profiles with sensory evaluation

Abstract: Various commercial tomato juices with different flavors are available at markets worldwide. To clarify the marker compounds related to the flavor characteristics of tomato juice, we analyzed 15 pure commercial tomato juices by a combination of volatile profiling and sensory evaluation. The correlations among volatiles and the relationship between volatiles and sensory descriptors were elucidated by multivariate analyses. Consequently, the tomato juices made from fresh market tomatoes (including the popular Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Since they were cultivated under the same soil and environmental conditions (no difference due to climatic effects) and possess similar dry matter (no dilution effects due to differences in fruit size), their differential accumulation of lycopene must be mainly due to the cultivar dependent genetic regulation of ripening. 9 Accordingly, Abushita et al 48 and Iijima et al 49 reported higher values of lycopene in processing tomato varieties as compared with fresh market varieties. While García-Valverde et al 50 determined higher lycopene content in tomatoes dedicated for fresh market (83.6-141.3 mg kg −1 ) than for processing purpose (83.8-97.6 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since they were cultivated under the same soil and environmental conditions (no difference due to climatic effects) and possess similar dry matter (no dilution effects due to differences in fruit size), their differential accumulation of lycopene must be mainly due to the cultivar dependent genetic regulation of ripening. 9 Accordingly, Abushita et al 48 and Iijima et al 49 reported higher values of lycopene in processing tomato varieties as compared with fresh market varieties. While García-Valverde et al 50 determined higher lycopene content in tomatoes dedicated for fresh market (83.6-141.3 mg kg −1 ) than for processing purpose (83.8-97.6 mg kg −1 ).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, Abushita et al . and Iijima et al . reported higher values of lycopene in processing tomato varieties as compared with fresh market varieties.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds 6-methyl-5-hepten-2-one, geranylacetone, β-ionone, pseudoionone and citral are derived from carotenoids by enzymatic cleavage (Tieman et al, 2006); 6-methyl-5-hepten-2-one was found in all tomato samples except the yellow cultivars, which is consistent with the fact that it is a lycopene-derived flavour. Iijima et al (2016) have found that the effects of aldehydes were positive, while cis-3-hexenol, hexanal and apocarotenoids had a negative effect on fresh tomatoes. The formation of carotenoid-related 6-methyl-5-hepten-2-one and geranylacetone was detected in the cultivar RB, which had higher lycopene content.…”
Section: Volatilesmentioning
confidence: 99%
“…For the characterization of volatile metabolite profiles by GC/MS-based metabolomics, we prepared a dataset as previously described (Iijima et al, 2016). Briefly, we processed the GC/MS raw data with GCMSsolution software (Shimadzu) and converted them into CDF files.…”
Section: Detection Of Volatile Compounds By Gc-msmentioning
confidence: 99%